A CASE SERIES OF SPONTANEOUS EXTRAPERITONEAL HEMORRHAGE IN COVID-19 PATIENTS IN MALAYSIA - Amir, Adib; Rajadurai, Arvin; Abdul Ghani, Zulkifli Zaki (Journal Of Cardiovascular, Neurovascular & Stroke, 2022)
Background: COVID-19 infection is associated with thrombotic events causing micro thrombosis and venous thromboembolism. Anticoagulant treatment has been shown to reduce mortality in COVID-19 cases and is routinely used. Spontaneous extraperitoneal hemorrhage (SEH), which includes retroperitoneal, iliopsoas or rectus sheath hematomas, is a known complication of anticoagulant use. Trans arterial embolization (TAE) is a safe and minimally invasive management option to control bleeding in SEH. We report 7 cases of SEH in COVID-19 patients admitted to Hospital Sungai Buloh. This case series highlights the occurrence of SEH in COVID-19 patients, its clinical and radiological manifestations and management pathways. Case presentation: All patients were on anticoagulants and presented with abdominal pain and/or swelling with sudden drop in hemoglobin. Computed tomography angiography (CTA) showed contrast extravasation indicative of active bleed. All patients proceeded with conventional transfemoral angiography with option of TAE. TAE was utilized in 6 out of 7 cases and was successful in achieving hemostasis with no procedure related complication. Conclusion: SEH should be suspected in COVID-19 patients on anticoagulants presenting with abdominal pain or drop in hemoglobin. CTA is confirmatory and TAE offers a viable and safe treatment option.